Facet joint disturbance induced by miniscrews in plated cervical laminoplasty: Dose it influence the clinical and radiologic outcomes?. Issue 38 (September 2016) - Chen, Hua; Li, Huibo; Wang, Beiyu; Li, Tao; Gong, Quan; Song, Yueming; Liu, Hao
Abstract : Abstract: A retrospective cohort study. Plated cervical laminoplasty is an increasingly common technique. A unique facet joint disturbance induced by lateral mass miniscrews penetrating articular surface was noticed. Facet joints are important to maintain cervical spine stability and kinetic balance. Whether this facet joint disturbance could affect clinical and radiologic results is still unknown. The objective of this study is to investigate the clinical and radiologic outcomes of patients with facet joints disturbance induced by miniscrews in plated cervical laminoplasty. A total of 105 patients who underwent cervical laminoplasty with miniplate fixation between May 2010 and February 2014 were comprised. Postoperative CT images were used to identify whether facet joints destroyed by miniscrews. According to facet joints destroyed number, all the patients were divided into: group A (none facet joint destroyed), group B (1–2 facet joints destroyed), and group C (≥3 facet joints destroyed). Clinical data (JOA, VAS, and NDI scores), radiologic data (anteroposterior diameter and Palov ratio), and complications (axial symptoms and C5 palsy) were evaluated and compared among the groups. There were 38, 40, and 27 patients in group A, B, and C, respectively. The overall facet joints destroyed rate was 30.7%. All groups gained significant JOA and NDI scores improvement postoperatively. The preoperative JOA, VAS, NDI scores, and postoperative JOA scores did not differ significantly among the groups. The group C recorded significant higher postoperative VAS scores than group A ( P = 0.002) and B ( P = 0.014) and had significant higher postoperative NDI scores than group A ( P = 0.002). The pre- and postoperative radiologic data were not significant different among the groups. The group C had a significant higher axial symptoms incidence than group A (12/27 vs 8/38, P = 0.041). Facet joints disturbance caused by miniscrews in plated cervical laminoplasty may not influence neurological recovery and spinal canal expansion, but may negatively affect postoperative axial symptoms.